High-power short-duration radiofrequency ablation for atrial fibrillation. (24th May 2021) - Kassa, K; Nagy, Z; Kesoi, B; Som, Z; Foldesi, C; Kardos, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: In recent times, high-power short-duration (HPSD) radiofrequency ablation (RFA) has emerged as an alternative strategy for pulmonary vein isolation (PVI) in atrial fibrillation (AF). Purpose: We aimed to compare HPSD approach and conventional, ablation-index (AI) guided PVI using contact force sensing ablation catheters in respect of efficacy, safety, procedural characteristics, and outcome. Methods: A total of 184 consecutive AF patients with first PVI were enrolled (age: 60 ± 11 years, paroxysmal: 56.5%, persistent: 43.5%) between November 2016 and December 2019. An ablation protocol of 50W energy with 15-20 g contact force was used for a duration of 8-12 sec based on the loss of capture concept in the HPSD group (n = 91) meanwhile, PVI was achieved according to the conventional power settings (posterior wall 25W, AI: 400, anterior wall 35W, AI: 550 ) in the control group (n = 93). During 1-year follow-up, documented AF for more than 30 seconds was considered as recurrence. Results: Radiofrequency time and procedural time were significantly shorter using HPSD ablation (26.0 ± 12.7 min vs. 42.9 ± 12.6 min, p < 0.001, and 91 ± 30.1 min vs. 105.3 ± 28 min, p < 0.001). The HPSD strategy significantly lowered fluoroscopy time and radiation dose (5.47 ± 4.07 min vs. 8.15 ± 10.04 min, p = 0.019, and 430.2 ± 534.06 cGycm2 vs. 604.2 ± 633.9 cGycm2, p = 0.046). The HPSD group showed significantly less arrhythmia recurrence during 1-year follow-up with 76.9% of patients free from AF compared to 66.7% in the control group (p = 0.037). No pericardial tamponade, periprocedural thromboembolic complication, or atrio-oesophageal fistula occurred in the HPSD group. We observed 2 pericardial tamponade and 1 periprocedural stroke in the control group. Conclusions: HPSD RFA for AF was demonstrated to be safe, and lead to significantly improved 1-year outcome in our mixed patient population. HPSD protocol significantly shortened procedural and radiofrequency time with decreased fluoroscopy time and radiation exposure.